The EU Financial Transactions Tax: Antecedents and Current Debate - Kitromilides, Yiannis; González, Ana Rosa (Panoeconomicus, 2013)
The paper deals with the development of the Financial Transactions Tax (FTT) policy idea and its feasibility in the absence of global coordination. New taxes are evaluated in terms of how they fit into existing national tax systems. Increasingly, however, cross-border issues assume greater significance in tax design and this is particularly pertinent in the case of FTT which has a long history. The various changes in tax systems and the economic environments within which they operate since the original “Tobin Tax” proposal are noted and the way they affect the debate on FTT are discussed. The proposal to introduce a unilateral FTT in the EU and its feasibility are examined. In terms of achieving its fundamental objectives the feasibility of the tax is crucial unless, as may be the case in the UK, the need to rebalance the economy away from the financial sector is a more urgent priority. Key words: Financial transactions tax, Tobin tax, Computerised financial trading, Global tax coordination. JEL: F31, G15.